Loss of IDO1 expression from human pancreatic β-cells precedes their destruction during the development of type 1 diabetes - Anquetil, F; Mondanelli, G; Gonzalez, N; Calvo, T; Gonzalo, J; Krogvold, L; Dahl-Jørgensen, K; Van Den Eynde, B; Orabona, C; Grohmann, U; Von Herrath, MG (American Diabetes Association, 2018)
Indoleamine 2,3 dioxygenase-1 (IDO1) is a powerful immunoregulatory enzyme that is deficient in patients with type 1 diabetes (T1D). In this study, we present the first systematic evaluation of IDO1 expression and localization in human pancreatic tissue. Although IDO1 was constitutively expressed in β-cells from donors without diabetes, less IDO1 was expressed in insulin-containing islets from double autoantibody-positive donors and patients with recent-onset T1D, although it was virtually absent in insulin-deficient islets from donors with T1D. Scatter plot analysis suggested that IDO1 decay occurred in individuals with multiple autoantibodies, prior to β-cell demise. IDO1 impairment might therefore contribute to β-cell demise and could potentially emerge as a promising therapeutic target.